Teaching History through Popular Literature Using Popular Movie Django Unchained (2012) - Bouaicha, Oumelkheir; Gasmi, Mustapha (Faculty of Letters and Foreign Languages Department of English, 2018)
This study aims to show how fiction movies, of popular literature that contains historical events, can take an important role to revive history classes, reduce the amount of boredom, and deliver history effectively. It was hypothesized that the boredom was and still the major obstacle that the learners face while studying history in addition to the teachers' methodology; the study hypothesized as well that the fictional movies are effective tool to deliver and engrave the history lectures in the students' minds, so that, popular literature would reach the point to be an effective method with using popular movies as a tool to teach history. The present study investigated second-year students’ opinions about the topic, and the results revealed that the majority of students admitted that the teachers' methodology is the reason for the rise of boredom during history class, while others reclaimed that it is not only the teachers' methods but also history itself. In another range, the study detected that the popular fiction movies helped to facilitate the difficult events, confusing dates and figures of history adding that movies, in general, revived the past with the motion pictures to the point where the one feels and lives history.